. Clinical Significance of NLRP3 Inflammasome and Related Cell Moleculesin early Elderly Diabetic Kidney Disease: NLRP3 Inflammasome and Related Cell Moleculesin - Shang, Yan (Journal of Medical Biochemistry, 2024)
Backgrounds：It aims to investigate the expression level of NLRP3 inflammasome and its related cell molecules in early diabetes kidney disease (EDKD) in the elderly and its clinical application value.Methods: From October 2021 to April 2023, 50 elderly patients with T2DM (T2DM group), 50 elderly patients with EDKD (EDKD group) and 50 elderly people who passed the health check-up (healthy group) are chosenas the study subjects. Plasma NLRP3 inflammasome and related cells (blood leukocyte count, monocyte count, lymphocyte count) molecular (NT-proBNP and others) levels are tested, and Pearson correlation analysis is utilized to explore the correlation among plasma NLRP3 inflammasome and related cells, molecules and renal function indicators (UACR, BUN, Ucr) in elderly patients with EDKD. Results: (1) The three groups’ comparison in HbA1c, FIns, HOMA-IR, UACR, BUN, Ucr, SOD, MCP-1 and TNF-α level were with P
Keywords: NLRP3 inflammasome; Early; Diabetes; Kidney disease; Clinical significance